2013
DOI: 10.1002/dta.1505
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and simple LC‐MS/MS screening of 64 novel psychoactive substances using dried blood spots

Abstract: The range of novel psychoactive substances (NPS) including phenethylamines, cathinones, piperazines, tryptamines, etc. is continuously growing. Therefore, fast and reliable screening methods for these compounds are essential and needed. The use of dried blood spots (DBS) for a fast straightforward approach helps to simplify and shorten sample preparation significantly. DBS were produced from 10 µl of whole blood and extracted offline with 500 µl methanol followed by evaporation and reconstitution in mobile pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 32 publications
0
43
0
5
Order By: Relevance
“…Despite the diffusion of NPS in the illicit market, to date few are the analytical methods dealing with the multianalyte screening of these compounds in biological fluids, probably due to the relative new occurrence of the phenomenon. Published methods are mainly LC-MS/MS applications and deal with NPS in different biological samples: oral fluid [24,41], hair [25,[42][43][44], urine [19,26,27,45,46], blood [28,47,48], serum [29,30]. The methods available in the literature generally deal with a single class of analytes, and are performed after extraction of samples by SPME, SPE, or liquid/liquid extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the diffusion of NPS in the illicit market, to date few are the analytical methods dealing with the multianalyte screening of these compounds in biological fluids, probably due to the relative new occurrence of the phenomenon. Published methods are mainly LC-MS/MS applications and deal with NPS in different biological samples: oral fluid [24,41], hair [25,[42][43][44], urine [19,26,27,45,46], blood [28,47,48], serum [29,30]. The methods available in the literature generally deal with a single class of analytes, and are performed after extraction of samples by SPME, SPE, or liquid/liquid extraction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, also in case of a positive result, the identification of the actual substance that can cross-react with the immunoassay must be carried out by a chromatographic/mass spectrometric technique, able to distinguish among similar structures and isomers. To overcome this problem, some screening methods based on chromatography coupled with mass spectrometry have been proposed [19][20][21][22][23][24][25][26][27][28][29][30]. The use of sophisticated techniques such as LC-MS/MS or GC-MS requires a clean-up step before the instrument analysis, especially when it is performed on highly complex matrices like blood.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that tasquinimod in spiked blood was stable on DBS cards for at least 24 months when stored at room temperature, as well as in whole blood stored at room temperature for 24 h. Also, ISR of DBS samples was shown to fulfil the 2/3/20 acceptance criteria. Acceptable stability for various compounds on DBS has been reported [17,18] and it has even been reported that DBS can increase stability for compounds found to be unstable in plasma [4,19].…”
Section: Discussionmentioning
confidence: 97%
“…Previously, good stability was described for up to 2 weeks at both RT and 4°C for amphetamine, MDMA, and methamphetamine while mephedrone was only stable when the DBS card was stored cooled. 24 Storage for 6 months at 4°C resulted in 50−75% of the initial concentrations measured for amphetamine, MDMA, and methamphetamine versus values between 84% and 96% when stored at −20°C. 25 In this study, analyte stability was evaluated after 5, 15, 30, and 50 days of storage at five different conditions: in sealed plastic bags at RT and 4 and −20°C, in a manual vacuum box at RT, and under nitrogen flow at RT (Figure S-2).…”
Section: Analytical Chemistrymentioning
confidence: 98%